Facile Enzymatic Synthesis of Ketoses. Issue 43 (14th August 2015) - Wen, Liuqing; Huang, Kenneth; Wei, Mohui; Meisner, Jeffrey; Liu, Yunpeng; Garner, Kristina; Zang, Lanlan; Wang, Xuan; Li, Xu; Fang, Junqiang; Zhang, Houcheng; Wang, Peng George
Abstract Studies of rare ketoses have been hampered by a lack of efficient preparation methods. A convenient, efficient, and cost‐effective platform for the facile synthesis of ketoses is described. This method enables the preparation of difficult‐to‐access ketopentoses and ketohexoses from common and inexpensive starting materials with high yield and purity and without the need for a tedious isomer separation step.